IEEE/RSJ International Conference on Intelligent Robots and System
DOI: 10.1109/irds.2002.1041705
|View full text |Cite
|
Sign up to set email alerts
|

Haptic control of a mobile robot: a user study

Abstract: We address rhe problem of releoperaiing a mobile robot using shared autonomy: an on-boardcontrollerperforms obstacle avoidance while the operator uses ihe manipulandwn of a haptic probe io designate rhe desired speed and rare of turn. Sensors on the robot are used ro measure obsracle range informiion. We describe a strategy to convert such range information into forces, which are re- jlecied io the operaior's hand, via rhe haptic probe. This hapric infomation provides feedback io the operator in addition to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Force feedback to the pilot is typically either environmental force [13] or the haptic boundary [1].…”
Section: A State Of the Art Haptic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Force feedback to the pilot is typically either environmental force [13] or the haptic boundary [1].…”
Section: A State Of the Art Haptic Controlmentioning
confidence: 99%
“…Obstacle avoidance and trajectory guidance control algorithms have been studied for terrestrial wheeled vehicles [5], [6] with force feedback generated by artificial force fields, typically virtual potentials or springdamper models associated with environmental interaction, that provides the user with a haptic sense of the local environment. In 2002 Lee et al [13] provided a user study that indicated that haptic feedback made a significant difference in the performance of a user in navigating through a complex obstacle strewn environment. The problem of force feedback teleoperation of a helicopter has been studied in the Faculty of Aerospace Engineering at Delft University of Technology over the last six years [2], [10], [12], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The P block represents the real pilot who produces the force f cm that acts directly on the Omega Device producing the displacement y m of the end-effector. This displacement is then converted, via the car-driving metaphor [11][12][13] (CD block), to a heading rate command used as a reference command, r m , for the aircraft heading rate, r s . The aircraft position (x e ,y e ) and its heading (ψ) are used by the environment block, E, to calculate the feedback signal F OA , based on the relative distance between the aircraft and the obstacles, in order to generate the haptic force for the master side; τ is the communication delay when present.…”
Section: Force-position Bilateral Teleoperationmentioning
confidence: 99%
“…A car-driving metaphor [11][12][13] for direct control of the UAV was employed. According to it, the operator uses the end-effector of the haptic device to designate the desired speed and rate of turn.…”
Section: A the Car-driving Metaphormentioning
confidence: 99%
“…16(3), 463-474 (2015) teleoperation, under-water tasks [9,10], obstacle avoidance through haptic interfaces [11][12][13], and ground robots tasks [14,15]. Moreover, Max Planck Institute (MPI) introduced technical issues to use KAKU Robocoaster for use as a realtime motion simulator [16].…”
Section: Introductionmentioning
confidence: 99%